2014
DOI: 10.1007/s00464-014-3954-3
|View full text |Cite
|
Sign up to set email alerts
|

Six month outcomes in patients experiencing weight gain after gastric bypass who underwent gastrojejunal revision using an endoluminal suturing device

Abstract: Six month follow-up for EGJR patients demonstrated a low-risk, minimally invasive treatment option to reverse weight gain subsequent to a failed gastric bypass. Procedures presented no complications and may provide an attractive alternative to standard surgical revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…No significant difference in weight loss was seen without or without pouch reduction in this cohort; however, these patients did not receive gastroplasty of their entire gastric pouch [15]. A separate group of investigators in a 16 patient study have reported more modest outcomes in patients undergoing endoscopic GJ stoma reduction using the Overstitch device with an average %EWL of 12.4 % at 6 months [14].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…No significant difference in weight loss was seen without or without pouch reduction in this cohort; however, these patients did not receive gastroplasty of their entire gastric pouch [15]. A separate group of investigators in a 16 patient study have reported more modest outcomes in patients undergoing endoscopic GJ stoma reduction using the Overstitch device with an average %EWL of 12.4 % at 6 months [14].…”
Section: Discussionmentioning
confidence: 72%
“…The majority of the weight loss observed in these studies occurred in the first 3-6 months after the procedure [12][13][14][15].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…10 It has been increasingly used to anchor stents within the GI lumen, 11 perform closure of perforations, 11 leaks, and fistulas, in addition to closure of mucosectomy after peroral endoscopic myotomy (POEM), 12,13 Natural Orifice Transluminal Endoscopic Surgery defect closures, 14 and perform primary and revision bariatric procedures. 15,16 This review will focus on endoscopic suturing with the OverStitch TM platform in the management of GI perforations, leaks and fistula.…”
Section: Endoscopic Versus Surgical Approach To Repairmentioning
confidence: 99%
“…Estudos posteriores comprovaram a superioridade da sutura de espessura total em relação à espessura parcial, de forma que esta última foi abandonada e seus dispositivos, retirados do mercado 113,114 . Também com o intuito de aprimorar a durabilidade, autores passaram a reportar a associação de métodos de ablação com a sutura endoscópica 115 . A plausibilidade biológica se respalda na observação cirúrgica que a aposição de mucosa com mucosa não gera fusão permanente dos tecidos 116 .…”
Section: Fatores Anatômicos/cirúrgicosunclassified